442 ICT01, an anti-BTN3A mAb that activates Vg9Vd2 T cells, plus interleukin-2: a potent and promising combination for cancer immunotherapy. (9th November 2020) - Gassart, Aude de; Brune, Patrick; Suong, LE; Agaugué, Sophie; Valentin, Emmanuel; Sims, Jennifer; Olive, Daniel; Frohna, Paul; Hoet, Rene
Abstract : Background gdT-cells are attractive targets for cancer immunotherapy given their strong cytolytic and pro-inflammatory cytokine secretion activities, and the association between tumor infiltration and positive prognosis. 1 2 ImCheck Therapeutics is developing ICT01, an anti-human butyrophilin-3A (BTN3A/CD277) mAb specifically activating g9d2 T-cells in a phosphoantigen (pAg)-independent manner. ICT01 is currently in a Phase 1/2a study in solid and hematologic tumors (NCT04243499 ).IL-2 has been shown to expand g9d2 T-cells in vitro and in non-human primates in presence of pAgs. 3 4 5 We wanted to characterize the proliferative effects of combining ICT01 with IL-2 on γ9δ2 T-cells as an approach to potentiate g9d2 T-cell mediated cancer immunotherapy. Methods g9d2 T-cell activation and expansion was assessed in vitro in human PBMCs treated with ICT01±IL-2, and in vivo, in the blood of immunocompromised NCG mice engrafted with 20 × 106 human PBMCs and treated with ICT01 (single IV dose, 5 mg/kg on Day 1) ±IL-2 (0.3MIU/kg IP on Day 1–4). A dose-ranging ICT01 (single IV dose, 1 or 5 mg/kg on Day 1)+IL-2 combination (1 MIU SC QD on Days 1–5) study was conducted in cynomolgus monkeys. Results: In PBMCs cultures in vitro, ICT01 selectively activated g9d2 T-cells and IL-2 significantly enhanced ICT01-mediated g9d2 T-cell proliferation, this compartment reaching >50% of T-cells after 8 days of treatment versus 10% with ICT01 alone. This was confirmed in vivo in mice models. Flow cytometry analysis of mice blood revealed a 5.5-fold increase in human g9d2 T-cell number in the combination groups compared to ICT01 or IL-2 alone treated animals, with g9d2 T-cell frequency reaching 35% of the CD3+ T-cell compartment. In Cynomolgus, a specific expansion and activation of peripheral g9d2 T-cells from 1–2% at baseline to up to 30% of T cells 7 days post ICT01 administration was observed. No ICT01 effect was observed on other immune cells. Histopathological examinations revealed a trend towards higher numbers of g9d2 T-cells in several organs in ICT01+IL-2 treated monkeys. There was no evidence for a systemic cytokine release syndrome at any time point. Adverse effects with variable severity were observed, most of them being reversible and commonly associated with IL-2 alone, and not reported in the IND-enabling GLP toxicity study with ICT01 monotherapy at doses up to 100 mg/kg. Conclusions: These results demonstrate the ability of ICT01+IL-2 combination to trigger profound γ9δ2 T-cell activation and expansion, suggesting that the clinical combination of ICT01 with a lymphoproliferative cytokine (e.g., IL-2) may be a novel therapeutic approach for cancer patients. Ethics Approval: Pseudonymized samples isolated from healthy volunteers: whole blood by ImCheck Therapeutics under the agreement n° 7173 between ImCheck Therapeutic SAS and EFS PACA (Etablissement Français du Sang Provence-Alpes-cote d'Azur) References: Gentles AJ, Newman AM, Liu CL, et al. The prognostic landscape of genes and infiltrating immune cells across human cancers. Nature Medicine 2015;21(8):938–945. Tosolini M, Pont F, Poupot M, et al. Assessment of tumor-infiltrating TCRVγ9Vδ2 γδ lymphocyte abundance by deconvolution of human cancers microarrays. OncoImmunology 2017;6(3):e1284723. Nada MH, Wang H, Workalemahu G, Tanaka Y, Morita CT. Enhancing adoptive cancer immunotherapy with Vγ2Vδ2 T cells through pulse zoledronate stimulation. Journal for ImmunoTherapy of Cancer 2017;5(1):9. Sicard H, Ingoure S, Luciani B, et al. In Vivo Immunomanipulation of Vγ9Vδ2 T cells with a synthetic phosphoantigen in a preclinical nonhuman primate model. The Journal of Immunology 2005;175(8):5471–5480. Ali Z, Shao L, Halliday L, et al. Prolonged (E)-4-Hydroxy-3-Methyl-But-2-Enyl pyrophosphate-driven antimicrobial and cytotoxic responses of pulmonary and systemic Vγ2Vδ2 T cells in macaques. The Journal of Immunology 2007;179(12):8287–8296.